Social Media and Africa's Public Sector Perspectives on Contemporary Issues - Adae, Eric Kwame; Kakra Twum, Kojo.; Hinson, Robert Ebo.; Duh, Helen Inseng; Odame, Doreen Anyamesem (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book focuses on developing a systematic approach to understanding the transformations in Africa's public sector social media landscape. Looking at the use of social media from the African public sector perspective, the authors present a comprehensive understanding of social media practices and how these could be integrated into African public sector institutions' operational activities in order to deliver greater value for African citizens and consumers of public goods and services. Chapters explore how social media in Africa differs from traditional media use, their application in the public sector, objectives for government using social media, and how social media plays an interactive role in e-government services. Providing practical guidance on the use of social media in Africa's public sector and governmental spaces, the book also serves as a teaching text in governance and public sector communication efforts within the African context for both undergraduate and graduate programmes. Eric Kwame Adae is Assistant Professor of Public Relations at the Drake University School of Journalism and Mass Communication, USA. Kojo Kakra Twum is Senior Lecturer in the Department of Business Administration and Economics at Presbyterian University College, Ghana. Robert Ebo Hinson is Pro Vice-Chancellor and Professor at the Ghana Communication Technology University. Helen Inseng Duh is Associate Professor and Head of the School of Business at the University of Witwatersrand, South Africa, and holds a Ph.D. in Marketing from Nelson Mandela University, South Africa. Doreen Nyarko Anyamesem Odame is Lecturer and examinations officer in the Department of General Studies (Faculty of Computing and Information Systems) at the Ghana Communication Technology University in Accra, Ghana.
Chapter 1: Overview of Social Media and Africa's Public Sector -- Chapter 2: Exploring Facets of Africa's Public Sector's Dance with Social Media -- Chapter 3: Main Objectives and Expectations for the Use of Social Media in the Public Sector in Africa -- Chapter 4: Catalysts for Social Media Adoption in the Public Sector in Africa -- Chapter 5: Democracy and Use of Social Media by Public Sector Organisations in Africa -- Chapter 6: Social Media and E-Government Services in Africa -- Chapter 7: The Way Forward for the Use of Social Media in the Public Sector in Africa.
Keywords: International economic integration; Globalization; Business; Africa; Management science; Public administration; Emerging Markets and Globalization; African Business; Business and Management; Public Sector Studies